2010
DOI: 10.5251/abjna.2010.1.3.175.184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diet (fatty acid and protein) content during spawning season on fertility, eggs and larvae quality of common porgy (Pagrus pagrus, Linnaeus 1758)

Abstract: Spawning in captivity of two red porgy's broodstock groups (Pagrus pagrus) of the same age was studied during one season. These two broodstock groups, designed A and B, were fed with different regimes during the spawning period. A group was fed on moist pellet while (A diet content 45% proteins, 10% lipids) B group was fed on fresh fish (A diet content 48 % protein, 8.7% lipids). The total eggs collected number for A group was 22 million eggs of which 18 million were viable, fertility was 474,966 eggs kg -1 fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…The greater composition of HUFA in the ASD may be another reason for their greater survival percentage in the current study. This result is concurrent with the findings of Abrehouch et al (), who confirmed that common porgy ( Pagrus pagrus ) broodstock that were fed fresh food consisting of shrimp, squid, and Boops boops exhibited considerably better survival percentages with regard to 2‐day embryos compared with broodstock fed with an artificial diet and sardines. The authors attribute this result to the proportion of n ‐3 HUFA in fish eggs, which should not be used as a sole criterion for assessing the quality of eggs.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The greater composition of HUFA in the ASD may be another reason for their greater survival percentage in the current study. This result is concurrent with the findings of Abrehouch et al (), who confirmed that common porgy ( Pagrus pagrus ) broodstock that were fed fresh food consisting of shrimp, squid, and Boops boops exhibited considerably better survival percentages with regard to 2‐day embryos compared with broodstock fed with an artificial diet and sardines. The authors attribute this result to the proportion of n ‐3 HUFA in fish eggs, which should not be used as a sole criterion for assessing the quality of eggs.…”
Section: Discussionsupporting
confidence: 89%
“…An improvement in broodstock nutrition has been shown to greatly improve not only the egg and sperm quality but also the seed production (both the quantity and the quality). Numerous studies have clarified and confirmed an improved fry quality through the enhancement of broodstock nutrition (Abdollahi, Heidari, & Aghamaali, ; Abrehouch, Ait, Chebbaki, Akharbach, & Idaomar, ; Aby‐ayad, Melard, & Kestemont, ; Dhert et al, ; Ershad, Mousavi‐Sabet, Falahatkar, & Moradkhani, ; Fernández‐Palacios, Norberg, Izquierdo, & Hamre, ; Furuita, Tanaka, Yamamoto, Suzuki, & Takeuchi, ; Izquierdo, Femandez‐Palacios, & Tacon, ; Wang & Zhang, ; Zhang, Wang, & Wang, ).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Abrehouch et al evaluated Pagrus pagrus spawning after fish were fed diets with different protein sources. The authors found significant differences in the hatching rate when using bogue (Boops boops) and squid, in contrast with sardine and pellets [36].…”
Section: Proteins Main Food Additivesmentioning
confidence: 97%